Avaliação da qualidade de vida e de transtorno mental comum em estudantes de uma escola médica durante o isolamento social na pandemia COVID-19 - Arar, Fabiano Cassaño (2022)
Introduction: Social isolation (SI) was one of the main actions adopted in Brazil when facing the COVID-19 pandemic, causing a change in the way of college teaching in Brazil, where face-to-face classes were suspended and remote teaching was authorized on an emergency basis. Stressor factors triggered by SI combined with the fact that medicine students have a deeper understanding of the disease and an uncertain environment experience with delay in clinical practice, altering their entire academic program, are potential triggers for mental disorders development with a direct impact on quality of life (QL). Objectives: To evaluate the QL and mental health (MH) of medical students at UNIFENAS-BH during social isolation in the COVID-19 pandemic. Methodology: This is a quantitative, cross-sectional and analytical study, which was conducted through a self-answered questionnaire containing questions that evaluate sociodemographic data, QL (WHOQOL-bref) and mental health (Goldberg's QSG-12) of medical students from UNIFENAS-BH between June and October 2020. For data analysis, the mental health and quality of life variables were calculated; descriptive analysis, descriptive statistics, univariate analysis using Student's t tests and Pearson's correlation analysis. The level of significance used was 5% (p < 0.05) and the Stata program version 11.1 was used. Results: The 565 students participating in the study perceived their QL as good, with the physical domain being worse and social relationships better. The prevalence of common mental disorder was high (66.9%) and as the worse the MH, the worse the students’ quality of life. The variables that had a negative impact on QL and MH were: lower income, being in the basic cycle, female gender and using self-reported medication. There was an improvement in QL and mental health over the course of the pandemic. Conclusions: Even though the perception of QL is good, the values obtained are close to the limits of a regular QL. In addition, the worsening in mental health of medical students during social isolation was high. In this way, assistance support measures for students, such as psychotherapeutic support, individual safety materials, financial and food subsidy, safe and non-sensationalist information and an efficient health system, in addition to new studies that evaluate the QL and mental health of students during a pandemic, are essential to minimize the psychological impacts suffered by this group and plan coping measures.